ANALISIS TINGKAT KEPUASAN WISATAWAN DOMESTIK TERHADAP KUALITAS PELAYANAN TICKETING PADA PT. INDONESIA AIR ASIA CABANG DENPASAR - Ayu Nugraheni, Putu; Sendra, I Made; Sasrawan Mananda, I GPB. (Jurnal IPTA (Industri Perjalanan Wisata); Vol 3 No 1 (2015): Jurnal IPTA (July 2015), 2015)
Tourists are given to choose many airlines which have their excellence. Tourist want to choose the cheaper price, but on the other hand they also want to have convenience on their travelling. Therefore, the competition among low cost carrier airlines caused many airlines begin to increase their facilities for their passangers such as, PT. Indonesia Air Asia. Datas in this research were collected by observation, interview, questionnaire and literature. Using accidental sampling with 65 domestic tourist respondences. While quality service dimentions are using tangibles, empathy, responsiveness, reliability and assurance. The result shows that factor of ticketing staffs performance in handling complaint is major priority with correspond to level 51,06% , the ability of ticketing staffs to give response to tourist needs become the second priority with correspond to level 54,38%. And the third priority is ability of ticketing staffs to give clear information with correspond to level 55,47%. Those factors have the lowest correspond level and have to take into priority for improvement process. While the factor which has the highest rate is the grooming performance of ticketing staffs with correspond to level 98,16%.
Keywords: Service Quality, Satisfaction of Travelers